Double Low-Dose Dual-Energy Liver CT in Patients at High-Risk of HCC: A Prospective, Randomized, Single-Center Study. Issue 6 (June 2020) - Yoon, Jeong Hee; Chang, Won; Lee, Eun Sun; Lee, Sang Min; Lee, Jeong Min
Abstract : Objectives: The aim of this study was to investigate the clinical feasibility of the simultaneous reduction of radiation and contrast doses using spectral computed tomography (CT) in patients at high-risk for hepatocellular carcinoma. Materials and Methods: Between May 2017 and March 2018, this prospective study recruited participants at risk of hepatocellular carcinoma with body mass indexes less than 30 and randomly assigned them to either the standard-dose group or the double low-dose group, which targeted 30% reductions in both radiation and contrast media (NCT03045445). Lesion conspicuity as a primary endpoint and lesion detection rates were then compared between hybrid iterative reconstruction (iDose) images of standard-dose group and low monoenergetic (50 keV) images of double low-dose group. Qualitative and quantitative image noise and contrast were also compared between the 2 groups. Participants and reviewers were blinded for scan protocols and reconstruction algorithms. Lesion conspicuity was analyzed using generalized estimating equation analysis. Lesion detection was evaluated using weighted jackknife alternative free-response receiver operating characteristic analysis. Results: Sixty-seven participants (male-to-female ratio, 59:8; mean age, 64 ± 9 years) were analyzed. Compared with the standard-dose group (n = 32), significantly lower CTDIvol (8.8 ± 1.7 mGy vs 6.1 ± 0.6 mGy) and contrast media (116.9 ± 15.7 mL vs 83.1 ± 9.9 mL) were utilized in the double low-dose group (n = 35; P < 0.001). Comparative analysis demonstrated that lesion conspicuity was significantly higher on 50 keV images of double low-dose group than on iDose images of standard dose on both arterial (2.62 [95% confidence interval (CI), 2.31–2.93] vs 2.02 [95% CI, 1.73–2.30], respectively, P = 0.004) and portal venous phases (2.39 [95% CI, 2.11–2.67] vs 1.88 [95% CI, 1.67–2.10], respectively, P = 0.005). No differences in lesion detection capability were observed between the 2 groups (figure of merit: 0.63 in standard-dose group; 0.65, double low-dose group; P = 0.52). Fifty kiloelectronvolt images of double low-dose group showed better subjective image noise and contrast than iDose image of standard-dose group on arterial and portal venous phases ( P < 0.001 for all). Contrast-to-noise ratio of the aorta and portal vein was also higher in double low-dose group than in standard-dose group ( P < 0.001 for all), whereas there was no significant difference of quantitative image noise between the 2 groups on arterial and portal phases ( P = 0.4~0.5). Conclusions: Low monoenergetic spectral CT images (50 keV) can provide better focal liver lesion conspicuity than hybrid iterative reconstruction image of standard-dose CT in nonobese patients while using lower radiation and contrast media doses. Abstract : Supplemental digital content is available in the text.